Biomass valorization of agriculture wastewater grown freshwater diatom Nitzschia sp. for metabolites, antibacterial activity, and biofertilizer. (June 2023) - Singh, Pankaj Kumar; Saxena, Abhishek; Tyagi, Rashi; Sindhu, Raveendran; Binod, Parameswaran; Tiwari, Archana
Graphical abstract: Highlights: Enhanced biomass productivity in Nitzschia sp. in agriculture wastewater. 2.1-fold increase in chrysolaminarin concentration of diatom in NPK. 1.2-fold enhancement in lipid content as compared to control. Strong antibacterial efficacy against five pathogenic bacteria. Plant growth promotion in Catharanthus roseus by diatoms biomass. Abstract: The sustainable utilization of agricultural wastewater is a major global challenge. This study evaluated the impact of agricultural fertilizer on the biomass potential of Nitzschia sp. for metabolite production, antibacterial activity, and slow release biofertilizer. Cultivation of Nitzschia sp. in agriculture wastewater (0.5 mg ml −1 ) exhibited maximum cell density (12×10 5 cells ml −1 ), protein content (10.0 mg g −1 ), and lipid content (14.96%). Carbohydrate and phenol content increases in a dose-dependent manner with 8.27 mg g −1 and 2.05 mg g −1 at a concentration of 2 mg ml −1 respectively. There was a 2.1-fold increment in chrysolaminarin content. Both gram-negative and gram-positive bacteria were susceptible to the antibacterial activity of the biomass. The effects of using diatom biomass as a biofertilizer were evaluated on the growth of periwinkle plants, which showed significant improvements in leaf development, branching at an early stage, flowering, and a marked increase in shoot length. Diatom biorefinery holds immense potential in addressing agriculture wastewater recycling and sustainable generation of high-value compounds.